2009
DOI: 10.1371/journal.pone.0006105
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Dehydrogenase-Elevating Virus Induces Systemic Lymphocyte Activation via TLR7-Dependent IFNα Responses by Plasmacytoid Dendritic Cells

Abstract: BackgroundLactate dehydrogenase-elevating virus (LDV) is a natural infectious agent of mice. Like several other viruses, LDV causes widespread and very rapid but transient activation of both B cells and T cells in lymphoid tissues and the blood. The mechanism of this activation has not been fully described and is the focus of the current studies.Principal FindingsA known inducer of early lymphocyte activation is IFNα, a cytokine strongly induced by LDV infection. Neutralization of IFNα in the plasma from infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 35 publications
2
48
0
Order By: Relevance
“…As mentioned earlier, these experiments required LDV+ FV. LDV could potently stimulate IFNα production (38), and removal of LDV in the FV/LDV stocks reduced IFNα upregulation at 18 to 24 h post-infection (38, 39). Since Type I IFNs could significantly induce Tetherin expression (27, 40), it is possible that LDV co-infection may have primed the host to express unusually high levels of Tetherin (38, 39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, these experiments required LDV+ FV. LDV could potently stimulate IFNα production (38), and removal of LDV in the FV/LDV stocks reduced IFNα upregulation at 18 to 24 h post-infection (38, 39). Since Type I IFNs could significantly induce Tetherin expression (27, 40), it is possible that LDV co-infection may have primed the host to express unusually high levels of Tetherin (38, 39).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the relatively weak association between Tetherin and T cell responses in the B 1 experiments led us to perform a second set of studies, this time with B6 WT and B6 Tetherin KO mice at 14 dpi. Since LDV co-infection could alter adaptive immune responses to FV (15, 29, 38, 39, 58), and the experimental design was not constrained by genetic parameters defined by classical FV infection studies (in contrast to the B 1 study), we utilized LDV-free FV stocks. Further strengthening the role of Tetherin as an antiretroviral factor in vivo , we observed significantly higher FV infection levels in Tetherin KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that lactate dehydrogenaseelevating virus (LDV) infection caused a polyclonal activation of CD19 ϩ B cells, characterized by the expression of the early activation marker CD69 in vivo (1). With the aim of studying mined by fluorescence-activated cell sorting (FACS) using FV glyco-Gag-specific monoclonal antibody clone 34 as described elsewhere (4).…”
Section: Inoculation Of Isolated Igmentioning
confidence: 99%
“…The resulting type I IFN response affects viral replication while simultaneously activating diverse immune effector cells (10). Specific ablation of pDCs during viral infection significantly diminishes the early type I IFN response (11)(12)(13)(14). During herpes simplex-1 and vesicular stomatitis virus infection, pDC depletion impairs CD8 + T cell immunity (12,15); similarly, during murine cytomegalovirus infection, the absence of pDCs results in diminished activation of early, nonspecific NK cells (12).…”
Section: Introductionmentioning
confidence: 99%